Incidence and Progression of Echocardiographic Abnormalities in Older Children with Human Immunodeficiency Virus and Adolescents Taking Antiretroviral Therapy: A Prospective Cohort Study. (4th May 2019) - Majonga, Edith D; Rehman, Andrea M; Mchugh, Grace; Mujuru, Hilda A; Nathoo, Kusum; Odland, Jon O; Ferrand, Rashida A; Kaski, Juan Pablo
Abstract: Background: A high prevalence of cardiac abnormalities has been reported in children with human immunodeficiency virus (HIV) taking antiretroviral therapy (ART) in sub-Saharan Africa. We investigated the incidence and progression of cardiac abnormalities among children taking ART in Zimbabwe. Methods: A prospective cohort study was conducted at a pediatric HIV clinic from 2014 to 2017. Children with HIV aged between 6 and 16 years and taking ART ≥6 months were enrolled. Transthoracic echocardiography was performed at baseline and after 18 months. Results: Of 197 participants recruited at baseline, 175 (89%; 48% female; median age 12 years, interquartile range 10–14 years) were followed up. The incidences of left and right heart abnormalities were 3.52 and 5.64 per 100 person-years, respectively. Stunting was associated with the development of any cardiac abnormality (adjusted odds ratio 2.59, 95% confidence interval 1.03–6.49; P = .043). Right ventricular (RV) dilatation persisted at follow-up in 92% of participants and left ventricular (LV) diastolic dysfunction in 88%. Cardiac abnormalities present at baseline reverted to normal over the follow-up period in 11 (6%). There was an overall increase in mean z scores for LV, left atrium (LA), RV, interventricular septum, and LV posterior wall diameters at 18 months ( P < .001). Conclusions: Despite ART, children with HIV have a high incidence of cardiac abnormalities, with only a minority being transient. Mean z scores for LV, LA, RV, interventricular septum, and LV posterior wall diameters increased over a relatively short follow-up period, suggesting the potential for progression of cardiac abnormalities. Longer follow-up is required to understand the clinical implications of these abnormalities. Abstract : Older children and adolescents with human immunodeficiency virus (HIV) who are receiving antiretroviral therapy in sub-Saharan Africa have a high incidence of echocardiographic abnormalities, which are likely primary HIV-related heart muscle disease and have the potential for progression over time.